1994
DOI: 10.1113/jphysiol.1994.sp020280
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for reactivation of the ATP‐sensitive K+ channel by MgATP complexes in guinea‐pig ventricular myocytes.

Abstract: 1. A mechanism underlying reactivation of the adenosine 5'-triphosphate-sensitive K+ (KATP) channels by MgATP complexes after run-down was examined in guinea-pig ventricular myocytes using the patch-clamp technique with inside-out patch configuration. 2. After run-down was induced by exposure of the intracellular side of the membrane patch to Ca2+ (1 mM), channel activity was reactivated by exposure and subsequent wash-out of MgATP (2 mM). Addition of inhibitors of various serine/threonine protein kinases to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…K NDP channels were active in cell-attached patches, and the transition to a nucleotide-free intracellular solution in the inside-out configuration resulted in a transient increase in their activity before they closed. These K NDP channels remained in an operational state and could be activated by MgUDP, known to be an effective stimulator but a poor inhibitor of K IR 6.2/SUR1 channels (15), which does not reactivate run-down channels like MgATP (16)). The rapid wash-out of ATP applied in the presence of Mg 2ϩ resulted in a transient increase in K NDP channel activity similar to that observed upon transition to the inside-out configuration.…”
Section: Resultsmentioning
confidence: 99%
“…K NDP channels were active in cell-attached patches, and the transition to a nucleotide-free intracellular solution in the inside-out configuration resulted in a transient increase in their activity before they closed. These K NDP channels remained in an operational state and could be activated by MgUDP, known to be an effective stimulator but a poor inhibitor of K IR 6.2/SUR1 channels (15), which does not reactivate run-down channels like MgATP (16)). The rapid wash-out of ATP applied in the presence of Mg 2ϩ resulted in a transient increase in K NDP channel activity similar to that observed upon transition to the inside-out configuration.…”
Section: Resultsmentioning
confidence: 99%
“…Although Mg-ATP is not required to mediate activation by anionic phospholipids, the anionic lipid hypothesis can account for the well known Mg-ATP activation effect on KATPs. It has previously been reported that nonphosphorylating analogs of ATP, AMP-PNP and AMP-PCP, are incapable of increasing KATP activity, suggesting that Mg-ATP acts as a phosphoryl group donor in kinase-mediated phosphorylation reaction, although such kinases have not yet been identified (29). Our effectiveness se- The open times were fitted to two components of the exponential.…”
Section: Discussionmentioning
confidence: 99%
“…47 We selected clearly striated cardiomyocytes with a length/width ratio of Ͼ4 and a resting membrane potential of ϷϪ70 mV (see Materials and Methods). Patches with channels displaying the mean PoϽ0.8 after patch isolation and/or reactivation by mmol/L MgATP, expected to refresh the channel maximally, 48 were discarded. For our expression studies, we used COSm6 cells that we have observed to have a negligible number of endogenous K IR , when compared with COS7, COS1, and HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%